Accelerated curing polyurethane adhesive composition
By using isocyanate-capped prepolymers and curing agent components with different curing kinetics in the adhesive, the shortcomings of existing adhesives in terms of curing speed and stability are solved, and the effect of rapid curing and uniform adhesive beads is achieved, ensuring safety and reliability after vehicle window replacement.
Patent Information
- Application Number
- CN202510089780.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2019-06-25
- Filing Date
- 2020-06-18
- Publication Date
- 2025-04-11
AI Technical Summary
Existing adhesives have shortcomings in curing speed and stability, especially when rapid curing is required after vehicle window replacement to ensure safety, while maintaining uniform adhesive beads and sufficient processability under different ambient conditions.
Using an adhesive composition comprising isocyanate-terminated prepolymer and curing accelerator, the curing accelerator comprises two curing agent components with different curing kinetics, a fast curing agent and a slow curing agent, mixed by a static mixer for rapid application and uniform distribution.
It achieves sufficient curing strength in a short time (such as 15 minutes) to allow rapid departure, while maintaining consistent adhesive beads and sufficient processability under different ambient conditions to ensure stable bonding and safe use of glass windows.
Smart Images

Figure CN119799253A_ABST
Abstract
Description
[0001] This application is a divisional application of application No. "202080045705.9" filed on June 18, 2020 and entitled "Accelerated Curing Polyurethane Adhesive Composition". Technical Field
[0002] The present invention relates to moisture-curable adhesive compositions for bonding glass to vehicles and buildings. In particular, the present invention relates to moisture-curable isocyanate-terminated prepolymer adhesive compositions coupled with a separate cure accelerator having two curing agent components with different cure kinetics, one having faster cure kinetics resulting in increased bead stability in the first few minutes and the other having slower cure kinetics allowing for adequate open time and rapid strength build-up. Background Art
[0003] One-component moisture-curing adhesive compositions have been used to bond windows to buildings and vehicles. Examples of adhesives used for these applications are described in USP 4,374,237; 4,687,533; 4,780,520; 5,063,269; 5,623,044; 5,603,798; 5,922,809; 6,015,475; 6,512,033; 6,657,035; 6,709,539; 7,101,950; 7,226,523; 7,361,292; 8,236,891; CA 2,564,992; and WO 2015 / 171307. In automotive factories, windows are installed using robotic and computer-controlled processes, which facilitates the use of a variety of high-performance adhesives, such as non-conductive adhesives and high modulus adhesives. The speed of cure is not a significant issue since new vehicles will not be driven any great distances within a few days of window installation.
[0004] In contrast, when a vehicle requires a window replacement, it is typically driven away shortly thereafter. The replacement is typically performed by an installer on the vehicle or remotely under uncontrolled conditions. Therefore, cure speed is important because vehicle owners want to drive their vehicles as quickly as possible after the windows are installed. One-component moisture-curing adhesives for replacement vehicle windows that facilitate a quick drive-away are described in USP 5,976,305; 6,709,539 and 7,226,523. Although these adhesives have established sufficient integrity to allow drive-away in a short period of time, they still require longer times to fully cure and may cure inconsistently depending on environmental conditions such as temperature and relative humidity.
[0005] Two-part compositions, one part comprising an isocyanate functional compound or prepolymer, and a compound and / or prepolymer having an isocyanate reactive component, are also used. It will be appreciated that the two parts, generally referred to as the A side and the B side, have substantially the same volume. Examples of two-part compositions, one part comprising an isocyanate functional compound or prepolymer and the other part comprising a compound and / or prepolymer having an isocyanate reactive component, are disclosed in EP 1,524,282 and USP 5,852,103; 6,709,539; 7,101,950 and 7,361,292. However, these tend to suffer from complex delivery systems to keep the two parts separate and require thorough mixing when dispensing to achieve a uniform product. Likewise, two-part adhesive compositions tend to react quickly and may form a skin, resulting in insufficient working time to properly position the replacement window under certain conditions (higher temperatures and higher relative humidity). Thus, even though two-part compositions may allow a car with replacement windows to be driven within 30 minutes of bonding the windows to the car, they generally do not allow for any faster drive-off times and care must be taken to ensure an even bead of adhesive.
[0006] More recently, WO 2012 / 151085 describes a two-part dual-cure adhesive composition comprising an isocyanate-terminated prepolymer (one part) and an acrylic acid acrylate monomer (the other part). In this composition, one part comprises an isocyanate-terminated polyether prepolymer and the other part comprises a hydroperoxide compound and acrylic acid or acrylate monomers, wherein the hydroperoxide compound is reduced to form free radicals when mixed with the other part to achieve sufficient integrity from the formation of the initial polyacrylic acid or polyacrylate matrix to allow a relatively fast drive-away time. However, the working time, bead consistency, processability, and final cure characteristics are not ideal.
[0007] It would therefore be desirable to have a fast drive-off adhesive for bonding glass into a structure that would cure sufficiently to allow drive-off in a short period of time (e.g., even 15 minutes) while also providing a consistent uniform adhesive bead and adequate workability (how long the glass can be placed and manipulated and still have adequate adhesion) under varying environmental conditions. Summary of the invention
[0008] In one embodiment, the present invention is a moisture-curable adhesive system comprising, consisting essentially of, consisting of: A) an isocyanate-terminated prepolymer and B) a curing accelerator comprising, consisting essentially of, consisting of: i) an isocyanate-reactive compound comprising: 1) a primary, secondary or tertiary amino group, or a primary thiol group and 2) an OH, NH and / or SH functionality of 2 to 7, and ii) a polyol having no primary, secondary or tertiary amino group, or a primary thiol group, wherein the polyol is selected from diols and / or triols, preferably wherein component B) is substantially free of water.
[0009] In a preferred embodiment of the present invention, the isocyanate-reactive compound (i) has an OH, NH and / or SH functionality of 2 to 4.5 and is present in an amount of less than 5% by weight of the curing accelerator (B).
[0010] Another embodiment of the present invention is a method of accelerating the curing of an adhesive composition, the method comprising, consisting essentially of, consisting of: a) providing a moisture-curable adhesive composition comprising: A) an isocyanate-terminated prepolymer and B) a curing accelerator comprising: i) an isocyanate-reactive compound comprising: 1) a primary, secondary, or tertiary amino group, or a primary thiol group and 2) 2 to 7 OH, NH, and / or SH functionalities, and ii) a polyol having no primary, secondary, or tertiary amino groups, or primary thiol groups, wherein the polyol is selected from diols and / or triols, preferably wherein component B) is substantially free of water, wherein the isocyanate-terminated prepolymer is provided, respectively. a) mixing the curing accelerator and the isocyanate-terminated prepolymer to form an adhesive mixture; c) applying the adhesive mixture to at least a portion of a first substrate; d) contacting the substrate having the adhesive mixture thereon with a second substrate such that the adhesive mixture is therebetween; and e) curing the adhesive mixture to bond the substrates together, preferably wherein the first substrate is a substrate wherein at least a portion of the substrate is an optically transparent substrate and the second substrate is a vehicle or a building, more preferably wherein the first substrate has an opaque portion, wherein the adhesive mixture is applied and contacted with the second substrate, preferably wherein the first substrate is glass or polycarbonate. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 is a graph of decking height versus time for Comparative Example A and Example 8.
[0012] Figure 2 is a graph of decking height versus time for Examples 9 to 11. DETAILED DESCRIPTION
[0013] The present invention is a formulation of an accelerated polyurethane adhesive that cures independently of humidity and a method of using the same. The adhesive of the present invention exhibits the curing properties of a 2K adhesive combined with the application properties of a 1K adhesive using a standard 1K application gun typically used for 1K polyurethane adhesive cartridges or casings or automated application equipment from a drum.
[0014] In one embodiment, the adhesive of the present invention is applied using either a 2K packaging solution (such as a peeler cartridge) or a casing in a casing solution, both of which can be used in a standard 1K application gun in combination with a static mixer, see, for example, USP 9,821,512, which is incorporated herein by reference. The use of a static mixer requires low viscosities of both adhesive components to allow for sufficiently fast application speeds.
[0015] In conventional adhesives, the low viscosity of the two components, which allows mixing with a static mixer, generally results in low stability of the bead against window sinking, sometimes referred to as planking performance. The present invention relates to the use of a low viscosity adhesive formulation which can rapidly increase in strength to allow windows to be planked onto the adhesive shortly after the adhesive is applied, while the increase in strength does not negatively affect the open time of the adhesive. This results in the length of time from when the adhesive has sufficient strength to hold the window (planking height ≤ 5.5 mm), and the length of time when the strength of the adhesive bead becomes too high to squeeze the window into the adhesive bead (planking height ≥ 1.7 mm) being at least 10 minutes or more. In the adhesive of the present invention, this is achieved by formulating the polyol component with two curing agents having different kinetics, one curing agent being "fast", resulting in an increase in bead stability within the first few minutes, while the second curing agent has "slow" curing kinetics, allowing sufficient open time and still rapid strength gain. Fast curing agents are isocyanate-reactive compounds, preferably polyols containing amines, preferably primary, secondary or tertiary amino groups and / or thiols, preferably primary thiol groups, wherein the isocyanate-reactive compounds preferably have an OH, NH and / or SH functionality of 2 to 7. Slow curing agents are polyols without primary, secondary or tertiary amino groups, or primary thiol groups selected from diols or triols, such as polyether diols or alkyl diols (e.g. 1,4-butanediol).
[0016] It has been found that the moisture-curable adhesive compositions of the present invention comprising isocyanate-terminated prepolymers can be cured in significantly shorter times while still having adequate working time and final cured properties required for installing aftermarket glass when repairing chipped or broken glass in a vehicle. Illustratively, the adhesive mixture can have a working time of 5, 8, 10 or even 15 minutes while being substantially cured in 60 minutes. Likewise, the methods of the present invention allow these moisture-curable adhesives to be consistently applied under widely varying environmental conditions.
[0017] The adhesive system of the present invention can be used to bond a variety of substrates together. Examples of substrates include plastics, glass, wood, ceramics, metals and coated substrates, such as plastics coated with a wear-resistant coating. The adhesive system of the present invention can be used to bond similar and different substrates together. The adhesive is particularly useful for bonding glass or plastics with a wear-resistant coating thereon to other substrates such as vehicles (e.g., cars) and buildings. The composition of the present invention can also be used to bond parts of modular components (e.g., vehicle modular components) together. Glass or plastics coated with a wear-resistant coating can be bonded to coated and uncoated parts of a vehicle.
[0018] The compositions of the present invention are particularly useful for bonding replacement windows into structures. The adhesive is pumpable, sag resistant, and bonds parts together at temperatures between -10°C and 45°C. Preferably, the composition has an uncured sample sag of less than 2 mm and a planking force between 1.5 pounds and 15 pounds under typical ambient conditions (i.e., temperatures of -10°C to 35°C and relative humidity of 25% to 75%). Preferably, the planking height from the time the adhesive has sufficient strength to hold the window to the time the strength of the adhesive bead is high enough to squeeze the window into the adhesive bead is equal to or less than 5.5 mm to equal to or greater than 1.0 mm.
[0019] This allows adhesives made from the compositions of the present invention to be applied over a wide range of ambient temperatures. No heating of the material is required to apply the adhesive. It has been unexpectedly discovered that an adhesive system can provide a unique combination of achieving suitable planking forces to allow a windshield to be placed soon after application, and hold long enough to allow repositioning, while curing quickly so that the vehicle can be driven away even after only 30 minutes.
[0020] Nominal as used with respect to functionality refers to the theoretical functionality, which can generally be calculated from the stoichiometry of the ingredients used. Typically, the actual functionality is different due to imperfections in the starting materials, incomplete conversion of reactants and formation of by-products.
[0021] Preferred polyisocyanates for preparing prepolymers include those disclosed in USP 5,922,809, column 3, line 32 to column 4, line 24, which is incorporated herein by reference. Preferably, the polyisocyanate is an aromatic or cycloaliphatic polyisocyanate, such as diphenylmethane-4,4'-diisocyanate, isophorone diisocyanate, tetramethylxylene diisocyanate, and most preferably diphenylmethane-4,4'-diisocyanate. Diols and triols are collectively referred to as polyols.
[0022] The prepolymer is made from polyols, such as diols and triols, such as those described in USP 5,922,809, column 4, line 60 to column 5, line 50. The polyols (diols and triols) are preferably polyether polyols, and more preferably polyoxyalkylene oxide polyols. The most preferred triols are ethylene oxide terminated polyols prepared by reacting glycerol with propylene oxide and then reacting the product with ethylene oxide.
[0023] It should also be understood that a small amount of other polyols can be used to form polyether prepolymers, such as polyester polyols, such as those known in the art. Typically, the presence of such other polyols can be up to 5 weight % of the polyols used to prepare the prepolymer. However, the prepolymer can be prepared in the absence of such polyols.
[0024] Isocyanate-terminated prepolymers can be prepared by any suitable method, such as bulk polymerization and solution polymerization. The reaction to prepare the prepolymer is carried out under anhydrous conditions, preferably under an inert atmosphere such as a nitrogen blanket, and to prevent the isocyanate groups from being crosslinked by atmospheric moisture. The reaction is preferably carried out at a temperature of 0°C to 150°C, more preferably at a temperature of 25°C to 90°C, until the residual isocyanate content determined by titrating the sample is very close to the desired theoretical value. "Isocyanate content" means the weight percentage of the isocyanate portion to the total weight of the prepolymer. The reaction to prepare the prepolymer can be carried out in the presence of a carbamate catalyst. Examples of such catalysts include stannous salts of carboxylic acids, such as stannous octoate, stannous oleate, stannous acetate, and stannous laurate. In addition, dialkyltin dicarboxylates, such as dibutyltin dilaurate and dibutyltin diacetate, are known in the art as carbamate catalysts, as are tertiary amines and tin mercaptides. Preferably, the reaction to prepare the prepolymer is catalyzed by stannous octoate. Depending on the nature of the isocyanate, the amount of catalyst used is generally between 0.005 and 5 parts by weight of the catalytic mixture. Preferably, the reaction is carried out in admixture with a plasticizer as described further below.
[0025] Moisture-curable adhesives also typically contain fillers such as carbon black. Depending on its structure and the molecular weight of the prepolymer, carbon black can vary over a wide range of structures given by the oil absorption number (ASTM D-2414-09). For example, carbon black typically desirably has an oil absorption number (OAN) of 80 to 200 ccs / 100 grams. Preferably, the carbon has an oil absorption number of at least 90, more preferably at least 100, and most preferably at least 110 to preferably at most 180, more preferably at most 165, and most preferably at most 150 ccs / 100 grams.
[0026] For a given carbon black, a suitable amount of carbon black can be determined. Typically, the amount of carbon black is at least 10 wt %, 15 wt %, up to 38 wt %, 35 wt %, 32 wt %, 30 wt % or 28 wt % by weight of the adhesive composition as needed.
[0027] The carbon black used may be standard carbon black which has not been specially treated to render it non-conductive. Standard carbon black is carbon black which has not been specially surface treated or oxidized. Alternatively, one or more non-conductive carbon blacks may be used exclusively or in combination with standard carbon black. Suitable standard carbon blacks include RAVEN TM 790、RAVEN TM 450、RAVEN TM 500、RAVEN TM 430、RAVEN TM 420 and RAVEN T 410 carbon black (available from Columbia) and CSX carbon blacks, such as ELFTEX S5100 and S7100, and MONARCH 120, 570, and 590 (available from Cabot), and PRINTEX TM 30 carbon black (available from Evonik Industries, Mobile, Alabama). Suitable non-conductive carbon blacks include RAVEN TM 1040 and RAVEN TM 1060 carbon black, available from Columbia Chemicals Co., Inc. (Marietta, Georgia).
[0028] Moisture-curable adhesives may also include reactive silicon. Reactive silicon may exist as a separate molecule such as silane. It may exist within the backbone or as an end group in the prepolymer. Reactive silicon is typically silicon that can be hydrolyzed, such as described in USP 6,613,816, column 4, lines 25 to 55. Other exemplary reactive silicones are described in U.S. Patent Publication 2002 / 0100550, paragraphs 0055 to 0065 and Hsieh, US6,015,475, column 5, line 27 to column 6, line 41.
[0029] When present in a moisture-curable adhesive, the amount of reactive silicon is typically 0.001 to 2 weight percent of the total weight of the adhesive composition. The amount of reactive silicon (note, the weight of the silicon itself, and not including, for example, organic groups attached thereto) can be at least 0.005%, 0.01%, 0.02%, 0.04%, 0.06%, 0.08%, or 0.1% to at most 1.8%, 1.6%, 1.4%, 1.2%, 1%, 0.8%, 0.5% of the adhesive composition.
[0030] Moisture-curable adhesives may also include one or more organic polymers dispersed therein. Preferably, the organic polymer is included in the prepolymer by including a dispersion triol in which organic polymer particles are dispersed. Dispersion triols are generally understood to have at least a portion of particles grafted with a polyol. Preferred dispersion triols are disclosed in Zhou's USP6,709,539, Column 4, Line 13 to Column 6, Line 18, which is incorporated herein by reference. Preferably, the triol used to disperse organic particles is a polyether triol, and more preferably a polyoxyalkylene triol. Preferably, such polyoxyalkylene oxide triols include polyoxypropylene chains with polyoxyethylene end caps. Preferably, the triol used has a molecular weight of 3,000 or greater, more preferably 4,000 or greater, and most preferably 5,000 or greater. Preferably, such triols have a molecular weight of 8,000 or less, and more preferably 7,000 or less. It is understood that the polyol (eg, triol) of the dispersion polyol is included in the polyol to prepare the prepolymer composition described herein, wherein the copolymer particles of the dispersion polyol are understood to be fillers in the composition.
[0031] Moisture curable adhesives typically further include plasticizers. Plasticizers can be used to modify rheological properties to desired consistency. Such materials should be water-free and inert to isocyanate groups. Plasticizers can be common plasticizers that can be used for polyurethane adhesive applications and are well known to those skilled in the art, and are hereinafter referred to as low-polarity plasticizers. Plasticizers are present in an amount sufficient to disperse the prepolymer terminated with isocyanate. Plasticizers can be added to prepolymers during the preparation of prepolymers or during the compounding process before prepolymers are placed in the first compartment. Preferably, plasticizers are present in 1 weight percent or more, more preferably 20 weight percent or more, and most preferably 30 weight percent or more of prepolymer formulations (prepolymers plus plasticizers). Preferably, plasticizers are present in 45 weight percents or less, and more preferably 35 weight percents or less of prepolymer formulations.
[0032] It is preferred to use two plasticizers, one of which is a high polarity plasticizer and one is a low polarity plasticizer. A high polarity plasticizer is a plasticizer with a polarity greater than that of an aromatic diester (e.g., phthalate). A low polarity plasticizer is a plasticizer with a polarity equal to or less than that of an aromatic diester.
[0033] Suitable high polarity plasticizers include one or more of alkyl esters of sulfonic acid, alkyl alkyl ether diesters, polyester resins, polyglycol diesters, polymeric polyesters, tricarboxylates, dialkyl ether diesters, dialkyl ether aromatic esters, aromatic phosphates, and aromatic sulfonamides. More preferred high polarity plasticizers include aromatic sulfonamides, aromatic phosphates, dialkyl ether aromatic esters, and alkyl esters of sulfonic acid. Most preferred high polarity plasticizers include alkyl esters of sulfonic acid and toluene sulfonamide. Alkyl esters of sulfonic acid include alkyl phenyl sulfonates available from Lanxess under the trademark MESAMOLL. Aromatic phosphates include PHOSFLEX TM 31L Isopropylated triphenyl phosphate, DISFLAMOLL TM DPO diphenyl-2-ethylhexyl phosphate, and DISFLAMOL TM TKP Tritolyl Phosphate. Dialkyl Ether Aromatic Esters including BENZOFLE TM 2-45 diethylene glycol dibenzoate. Aromatic sulfonamides including KETJENFLE TM 8 o and p, N-ethyltoluenesulfonamide.
[0034] Suitable low polarity plasticizers include one or more of aromatic diesters, aromatic triesters, aliphatic diesters, epoxidized esters, epoxidized oils, chlorinated hydrocarbons, aromatic oils, alkyl ether monoesters, naphthenic oils, alkyl monoesters, glyceride oils, paraffin oils, and silicone oils. Preferred low polarity plasticizers include alkyl phthalates, such as diisononyl phthalate, dioctyl phthalate, and dibutyl phthalate, partially hydrogenated terpenes (commercially available as "HB-40"), epoxy plasticizers, chloroparaffins, adipic acid esters, castor oil, toluene, and alkyl naphthalenes. The most preferred low polarity plasticizer is alkyl phthalate.
[0035] The amount of low polarity plasticizer in the adhesive composition is an amount that provides the required rheological properties and is sufficient to disperse the catalyst in the system. The amount disclosed herein is included in those amounts added during the preparation of the prepolymer and during the blending of the adhesive. Preferably, the low polarity plasticizer is used in an amount of 5 weight parts or more, more preferably 10 weight parts or more, and most preferably 18 weight parts or more based on the weight of the moisture-curable adhesive. The low polarity plasticizer is preferably used in an amount of 40 weight parts or less, more preferably 35 weight parts or less, and most preferably 30 weight parts or less based on the total amount of the moisture-curable adhesive.
[0036] The amount of high polarity plasticizer in moisture-curable adhesive is the amount that imparts the required rheological properties and acceptable sagging and drawing properties to the dispensed moisture-curable adhesive. Preferably, high polarity plasticizer (if used) is used in moisture-curable adhesive in an amount of 0.2 parts by weight or more, more preferably 0.5 parts by weight or more, and most preferably 1 part by weight or more, based on the weight of the moisture-curable adhesive. High polarity plasticizer is preferably used in an amount of 20 parts by weight or less, more preferably 12 parts by weight or less, and most preferably 8 parts by weight or less, based on the total amount of the moisture-curable adhesive.
[0037] Moisture-curable adhesives may further include polyfunctional isocyanates, for example, to improve the modulus of the composition in cured form or the adhesion of the adhesive composition to a particular substrate such as a painted substrate. "Polyfunctional" as used in the case of isocyanates refers to isocyanates having a functionality of 2 or more. Polyisocyanates can be any monomeric, oligomeric or polymeric isocyanates with a nominal functionality of 2 or more. More preferably, polyfunctional isocyanates have a nominal functionality of 2.7 or more. Preferably, polyfunctional isocyanates have a nominal functionality of 5 or less, even more preferably 4.5 or less and most preferably 3.5 or less.
[0038] The polyisocyanate may be monomeric; a trimerized isocyanurate or biuret of a monomeric isocyanate; an oligomeric or polymeric reaction product of several units of one or more monomeric isocyanates. Examples of preferred polyfunctional isocyanates include trimers of hexamethylene diisocyanate, such as those available from Bayer under the trade names DESMODUR N3300 and N100, and polymeric isocyanates, such as polymeric MDI (methylene diphenyl diisocyanate), such as those sold under the trade name PAPI by The Dow Chemical Company, including PAPI 580N polymeric isocyanate. The polyfunctional isocyanate, when present, is typically present in an amount sufficient to affect the modulus of the cured composition of the present invention or to improve adhesion to certain substrates described above.
[0039] The polyfunctional isocyanate, when present, is preferably present in an amount of 0.5 parts by weight or more, more preferably about 1.0 parts by weight or more, and most preferably about 2 parts by weight or more, based on the weight of the moisture-curable adhesive. The polyfunctional isocyanate is preferably present in an amount of 12 parts by weight or less, more preferably 8 parts by weight or less, and most preferably about 4 parts by weight or less, based on the weight of the moisture-curable adhesive.
[0040] The moisture-curable adhesive may also include a catalyst that catalyzes the reaction of the isocyanate moiety with water or a compound containing active hydrogen. Such compounds are well known in the art. The catalyst may be any catalyst known to those skilled in the art for the reaction of the isocyanate moiety with water or a compound containing active hydrogen. Among the preferred catalysts are organotin compounds, metal alkanoates and tertiary amines. Mixtures of various types of catalysts may be used. A mixture of a tertiary amine and a metal salt is preferred. Even more preferred are tertiary amines, such as dimorpholinyl diethyl ether or triethylenediamine, and metal alkanoates, such as bismuth octoate or dimethyltin dineodecanoate. Included among the useful catalysts are organotin compounds, such as alkyl tin oxides, stannous alkanoates, dialkyl tin carboxylates and tin mercaptides. Stannous alkanoates include stannous octoate. Alkyl tin oxides include dialkyl tin oxides, such as dibutyl tin oxide and its derivatives. The organotin catalyst is preferably dialkyl tin dicarboxylates or dialkyl tin dithiolates. Dialkyl tin dicarboxylates having lower total carbon atoms are preferred because they are more active catalysts in the compositions of the present invention. Preferred dialkyl dicarboxylates include dimethyltin 1,1-dilaurate, dibutyltin 1,1-diacetate, and dimethyl 1,1-dimaleate. Preferred metal alkanoates include bismuth octoate or bismuth neodecanoate.
[0041] The organotin or metal alkanoate catalyst is typically present in an amount of 60 parts per million or more, preferably 120 parts per million or more up to 1.0 weight percent, preferably 0.5 weight percent, and more preferably 0.1 weight percent, based on the total weight of the moisture-curable adhesive.
[0042] Useful tertiary amine catalysts include dimorpholino dialkyl ethers, di((dialkylmorpholino)alkyl)ethers, bis-(2-dimethylaminoethyl)ether, triethylenediamine, pentamethyldiethylenetriamine, N,N-dimethylcyclohexylamine, N,N-dimethylpiperazine 4-methoxyethylmorpholine, N-methylmorpholine, N-ethylmorpholine and mixtures thereof. A preferred dimorpholino dialkyl ether is dimorpholino diethyl ether. A preferred di((dialkylmorpholino)alkyl)ether is (di-(2-(3,5-dimethylmorpholino)ethyl)ether). Tertiary amines, if used, are preferably used in amounts of 0.01 parts by weight or more, more preferably 0.05 parts by weight or more, even more preferably 0.1 parts by weight or more, and most preferably 0.2 parts by weight or more, and 2.0 parts by weight or less, more preferably 1.75 parts by weight or less, even more preferably 1.0 parts by weight or less, and most preferably 0.4 parts by weight or less, based on the weight of the moisture-curable adhesive.
[0043] Moisture-curable adhesives can be formulated with fillers and additives other than carbon black known in the prior art for use in adhesive compositions. By adding such materials, physical properties such as viscosity, flow rate, etc. can be changed. However, in order to prevent premature hydrolysis of the moisture-sensitive groups of the isocyanate-terminated prepolymer, the filler should be thoroughly dried before mixing with it. Other exemplary fillers include clay, titanium dioxide, calcium carbonate, surface-treated silica, titanium oxide, fumed silica, talc, wollastonite, etc. In an embodiment, more than one reinforcing filler can be used.
[0044] Moisture-curable adhesive can also have a stabilizer, which inhibits and prevents premature crosslinking of isocyanates in the adhesive. Stabilizers known to the technician for moisture-curable adhesives can be used. The example of stabilizer includes diethyl malonate, alkylphenol alkylate, p-toluenesulfonic acid isocyanate, benzoyl chloride and ortho-alkyl formate. Stabilizer is typically used in an amount of 0.1 weight part or more, preferably 0.5 weight part or more and more preferably 0.8 weight part or more based on the gross weight of the moisture-curable adhesive. Such stabilizer is used in an amount of 5.0 weight parts or less, more preferably 2.0 weight parts or less and most preferably 1.4 weight parts or less based on the weight of the adhesive.
[0045] Other components commonly used in adhesive compositions may be used in moisture-curable adhesives. Such materials are well known to those skilled in the art and may include UV stabilizers, antioxidants, heat stabilizers, and the like.
[0046] Moisture-curable adhesives can be prepared by blending the components together using means well known in the art. Typically, the components are blended in a suitable mixer. Such blending is preferably carried out in an inert atmosphere in the absence of oxygen and atmospheric moisture to prevent premature reactions. In embodiments where a large amount of polyester-based isocyanate-functional prepolymers are used, the adhesive composition can be blended at a temperature higher than the melting point of the polyester-based isocyanate-functional prepolymer and lower than the temperature at which significant side reactions occur. In this embodiment, the temperature used is 40°C to less than about 90°C and more preferably 50°C to 70°C. Once the adhesive composition is formulated, it is packaged in a suitable container so as to protect it from atmospheric moisture and oxygen. Contact with atmospheric moisture and oxygen may cause premature crosslinking of the polyurethane prepolymer containing isocyanate groups.
[0047] The adhesive system also includes a fast curing accelerator, which includes an isocyanate-reactive compound, such as a polyether or a polyol, which has an amino group in the main chain of the polyol. The isocyanate-reactive compound may have a terminal OH group and at least one amino group in its main chain. The isocyanate-reactive compound with an amino group generally has an average OH functionality (total OH moles / total polyol moles) greater than 2 to 5. The average OH functionality is preferably equal to or greater than 2.2, 2.5, 3.0, 3.5 or 3.8, and equal to or less than 4.8, 4.5 or 4.2.
[0048] The isocyanate-reactive compound with amino group has at least one amino group in its main chain. The main chain can be the same as the polyol for preparing the isocyanate-terminated prepolymer (e.g., aliphatic polyether or polyester main chain). The isocyanate-reactive compound with amino group can be formed by initiating the formation of polyol using a multifunctional amine compound. Usually, the amino groups present in the main chain are basically tertiary amines.
[0049] The average amount of amino groups in the isocyanate-reactive compound having amino groups is generally 1 to 6. Preferably, the average amount of amino groups present in the polyol having amino groups is at least 1.5, 2, 3.0, 3.5 or 3.8 to at most 4.8, 4.5 or 4.2.
[0050] Likewise, the OH value (OH#) of the isocyanate-reactive compound having an amino group can be any useful value for achieving the desired cure rate and processability. Typically, the OH# is at least 25 to 2000. Preferably, the OH value is at least 100, 250, 500 or even 550. The OH value is derived from a wet analysis method of the hydroxyl content of the polyol; it is the number of milligrams of potassium hydroxide equivalent to the hydroxyl content in one gram of polyol or other hydroxyl compound, and is given by the following equation:
[0051]
[0052] Where 56.1 is the atomic weight of potassium hydroxide, and 1000 is the number of milligrams in one gram of sample.
[0053] The isocyanate-reactive compound having an amino group may also have any useful molecular weight. Typically, the molecular weight of the polyol is at least 200 to 10,000. Preferably, the molecular weight is at most 5000, 3000, 1500, 1000, 500 or even 400. Preferably, the molecular weight is at least 100, 200 or 250. In a preferred embodiment, the isocyanate-reactive compound having an amino group has an average OH functionality of 3.5 to 4.2 and an OH value of at least 500.
[0054] The curing accelerator may include a small amount of water, as long as it does not adversely affect the curing rate, processability and curing properties of the adhesive mixture, such as causing bubbling. The amount of water in the curing accelerator is generally less than 1% of the total weight of the curing accelerator and the moisture-curable adhesive. Typically, it is desirable that the amount of water is as low as possible, such as only a trace amount, such as 500 parts per million by weight of the total weight of the moisture-curable adhesive and the curing accelerator. Preferably, the water content is determined using known methods, and the amount of water is at most 100 ppm to anhydrous or substantially anhydrous.
[0055] The curing accelerator may include one or more other ingredients, such as fillers, polyols without amino groups in the backbone, catalysts, plasticizers, rheology modifiers, UV stabilizers, or other useful ingredients for moisture-curable adhesives. The fillers, polyols, plasticizers, and catalysts may be any of those previously described or known in the art. The amount of each of these may be determined by the desired amount of isocyanate-reactive groups (e.g., OH) and other physical properties such as rheological properties, which is useful for ensuring uniform mixing and application of the adhesive system.
[0056] When fillers, amino-free polyols, catalysts and plasticizers are included in the curing accelerator, they are typically present in the following amounts. The isocyanate-reactive compound with amino groups will typically be present in an amount of 5% to 50% by weight of the curing accelerator. The amino-free polyol will typically be present in an amount of 20% to 80% by weight of the curing accelerator. The filler or filler combination will typically be present in an amount of 10% to 35% of the curing accelerator. The catalyst or catalyst combination will typically be present in an amount of 0.01% to 2% of the curing accelerator.
[0057] The curing accelerator is used to accelerate the curing of the moisture-curable adhesive. When doing so, the curing accelerator and the moisture-curable adhesive are provided separately, otherwise they will react before application. Any suitable method of providing two reactive materials with different volumes that are subsequently mixed can be used, such as the method described in the co-pending application U.S. Application No. 61 / 977668 of Zhu et al., known in the art and filed on April 10, 2014, page 1, line 10 to page 2, line 8. Preferably, the moisture-curable adhesive and the curing accelerator are provided in the two-component reactive distribution system described in the above-mentioned U.S. application.
[0058] Since the moisture-curable adhesive contains an isocyanate-terminated prepolymer and is moisture-curable, the isocyanate index of the adhesive system (i.e., the amount of isocyanate / reactive group in the curing accelerator multiplied by 100) is generally 85 to 200, but preferably 100 to 170. Likewise, since a moisture-curable adhesive is used, the volume ratio of the curing accelerator to the moisture-curable adhesive is generally 5 or 10 to 200, 100, 50 or 20. The iso index of all examples and comparative examples is substantially the same.
[0059] Mixing, applying, contacting and allowing to cure the moisture-curable adhesive and curing accelerator can be accomplished by any suitable method, such as methods known in the art, including the methods described in the above-mentioned U.S. applications. Preferably, mixing, applying, contacting is performed using the methods of the above-mentioned U.S. applications.
[0060] The adhesive system of the present invention can be used to bond a variety of substrates together. The adhesive system can be used to bond porous and non-porous substrates together. The adhesive system is applied to the substrates and thereafter the adhesive on the first substrate is contacted with the second substrate. In a preferred embodiment, the surface to which the adhesive is applied is cleaned and may be primed prior to application, but a primer is not necessary, see, for example, USP 4,525,511; 3,707,521 and 3,779,794; for typical application practices.
[0061] Typically, the adhesive system is applied under typical ambient conditions (23°C ± 10°C) in the presence of atmospheric humidity (typically 20% to 99% relative humidity). For testing the curing behavior, a relative humidity of 50% ± 5% at 23°C ± 2°C is suitable. Curing can be accelerated by adding additional water to the atmosphere or by applying heat during the curing of the adhesive by means of convection heating, microwave heating, etc.
[0062] The adhesive system is preferably used to bond glass or plastic coated with a wear-resistant coating to other substrates such as metal or plastic. In a preferred embodiment, the first substrate is a glass window or a plastic window coated with a wear-resistant coating, and the second substrate is a window frame. In another preferred embodiment, the first substrate is a glass window or a plastic window coated with a wear-resistant coating, and the second substrate is a window frame of a car. Preferably, the glass window is cleaned before bonding. The plastic coated with the wear-resistant coating can be any transparent plastic, such as polycarbonate, acrylic resin, hydrogenated polystyrene or a hydrogenated styrene conjugated diene block copolymer with a styrene content greater than 50%. The coating can include any wear-resistant coating, such as a polysiloxane coating. Preferably, the coating has an ultraviolet coloring light blocking additive. Preferably, the glass or plastic window has an opaque coating, which is arranged in the area to be contacted with the adhesive to prevent UV light from reaching the adhesive.
[0063] In a preferred embodiment, the adhesive system is used to replace windows in a structure or vehicle, and most preferably in a vehicle. The first step is to remove the previous window. This can be achieved by cutting the adhesive bead that holds the old window in place, and then removing the old window. Thereafter, the new window is cleaned and primed (if necessary). The old adhesive on the window flange can be removed, although this is not necessary, and in most cases it is left in place, but it can be cut flat with a cutting tool. The window flange can be primed with a base paint, but it is not necessary. The adhesive system is applied to the periphery of the window in the form of beads, and the window is positioned so that when placed in a vehicle, it will contact the window flange. The window on which the adhesive is located is then placed in the flange, wherein the adhesive is located between the window and the flange. Alternatively, the adhesive can be applied to the window flange. The adhesive bead is a continuous bead, and its function is to seal the joint between the window and the window flange. The continuous bead of adhesive is a bead positioned so that the beads are connected at each end to form a continuous seal between the window and the flange when in contact. Thereafter, the adhesive is cured.
[0064] The adhesive system can also be used to bond large mass substrates of more than 20 Kg up to 120 Kg to other substrates. In one type of large mass substrate, the substrate is a large window, such as a large window for a public transportation vehicle (eg, a bus or train).
[0065] In some applications, the adhesive system can be used together with a primer or an activating wipe. The primer or activating wipe is typically applied to the surface of the substrate. Any solvent is allowed to evaporate, and then the adhesive system is contacted with the substrate. Preferably, the time period from applying the primer or activating wipe to applying the adhesive system to the substrate is 0.5 minute or longer, more preferably 1 minute or longer, and most preferably 2 minutes or longer.
[0066] Examples
[0067] The following examples are provided to illustrate the present invention but are not intended to limit its scope. Unless otherwise indicated, all parts and percentages are by weight. The raw materials used in the moisture-curable adhesive and the non-reactive components used in the curing accelerator are shown in Table 1.
[0068] Table 1
[0069]
[0070]
[0071] * Prepolymer T-721 is an isocyanate functional polyester prepolymer prepared by mixing 46.7 g of plasticizer (branched plasticizer), 30.15 g of isocyanate (diphenylmethane 4,4'-diisocyanate) commercially available under the trade name Isonate M125U and 190.0 g of polyester polyol commercially available under the trade name DYNACOL 7381. The entire mixture was then stirred at 70°C under N2 for 8 hours.
[0072] Examples 1 and 2 are isocyanate components (A side) formulated to have the same Ballan viscosity with the following composition (amounts are weight percentages). The compositions of Examples 1 and 2 are shown in Table 2. In Table 2, the Ballan viscosity is measured from materials conditioned at 23°C. The materials in the measuring cup and storage container are conditioned in a water bath at 23°C for a minimum of 1 hour. After the material in the measuring cup is transferred air-free, the measuring cup is mounted on the ballan measuring device. The adhesive is extruded through a nozzle with a diameter of 2 mm and a length of 1.8 mm at a pressure of 4±0.01 bar. The weight of each extrusion is measured. The pressure flow viscosity is calculated in g / min.
[0073] Table 2
[0074]
[0075] Examples 3 to 6 are polyol components (B side) containing a curing agent. The amounts of each component are listed in weight percent.
[0076] Example 3 contained only a "slow" curing agent (ie, 1,4-butanediol in combination with a higher molecular weight polyether triol).
[0077] Examples 4 to 6 contain a "slow" curing agent, a "fast" curing agent that reacts directly after mixing with the isocyanate groups of the isocyanate component. In Examples 4 and 5, the fast curing agent is an increasing amount of a polyether diamine.
[0078] Example 6 contains an alcohol containing a tertiary amine, which intramolecularly catalyzes the reaction of the alcohol with the isocyanate, making these OH groups faster than the corresponding OH groups of 1,4-butanediol.
[0079] The compositions of Examples 3 and 6 are shown in Table 3.
[0080] Table 3
[0081]
[0082] Referring to Table 2, isocyanate component Example 1 and Example 2 are made by the following procedure: Components 1 and 3 are added to a mixer and degassed under vacuum for 40 minutes. After pre-drying, item 4 is added to the mixer and mixed at a low speed for 5 minutes under vacuum until they are fully wetted by other items. The speed of the mixer is slowly increased to disperse item 4 (carbon black) for 40 minutes under complete vacuum. The mixture is then heated to 65°C under stirring. Component 2 is added after being preheated to the same temperature of 65°C. Then the heating is turned on and cooling is started to cool to 40°C. Components 5 to 10 are then added and mixed for another hour under vacuum. The mixer is then cooled to ambient temperature, and the moisture-curable adhesive is discharged into a container under dry conditions.
[0083] Table 4 shows curing accelerator examples and comparative examples. Each of these is prepared by the following substantially identical procedures. With reference to Table 3, components 1 and 4 are added to a mixer and degassed for 30 minutes under vacuum. Then pre-dried components 5 to 8 are added and slowly mixed at a low speed for 5 minutes under vacuum until they are fully wetted by other articles. The speed of the mixer is slowly increased to disperse the added components 5 to 8 for 40 minutes under complete vacuum. Finally, articles 2 and 3 are added and mixed for 20 minutes under vacuum. The mixture is then discharged into a sealed container.
[0084] Each curing accelerator formulation shown in Table 4 was placed into an adhesive dispensing system (two-component casing) together with the above-mentioned moisture-curable adhesive described in Example 1 of the above-mentioned U.S. Application No. 61 / 977,668. The volume ratio of moisture-curable adhesive to curing accelerator was 9 to 1. For each example and comparative example, the isocyanate index was substantially the same. The moisture-curable adhesive and curing accelerator were dispersed in the same manner as described in Example 1 of the above-mentioned U.S. application.
[0085] The compositions of Comparative Example A and Examples 8 to 11 are shown in Table 4.
[0086] The following properties of Comparative Example A and Examples 8 to 11 were measured and reported in Table 4:
[0087] Use penetrometer to measure "planking" performance. Apply triangular adhesive beads with a nozzle with a triangular shape, the bottom of the nozzle is 7mm and the height is 14mm. A weight of 115g (100g weight+15g connecting rod) is accurately fixed to the tip of the adhesive bead. Release the grip of the weight for 5 seconds and allow it to sink into the adhesive bead. The penetration depth is measured in millimeters. The penetration depth is measured directly 1 minute after applying the adhesive bead, and then measured every 2 minutes until it is no longer possible to easily squeeze the adhesive. The direct planking performance of the adhesive after mixing in a static mixer at time 0 is predicted by a linear approximation of the time when the adhesive can be squeezed or the penetration depth of the first 20 minutes at most;
[0088] "Impact Strength" is determined by GEX Method 344. A metal specimen is placed in a sample holder. The adhesive is applied between the tips, allowing it to overflow onto the tape. Then, a specimen (76x25x5mm) is placed on top of the tips, and the adhesive on top is slowly removed with a spatula, maintaining a perfect shape of the bead (25x13x5mm). Afterwards, the specimen is stored for the desired curing time (e.g. 15min and 30min) and under ambient conditions. Then, the impact pendulum is raised and locked, holding the specimen in place, and the hammer is released (a 10lb hammer is used). The total energy that the adhesive can withstand before destructive failure is measured in J;
[0089] "Lap shear strength" is measured according to DIN EN 527 on a suitable device (e.g. shear strength device Zwick 1435 with FHM 8606.00.00 or 8606.04.00 mounting device). Adhesive bond dimensions of 10×25×1.5 mm are used for lap shear specimens. Lap shear specimens are tested after 1 h, 2 h, 4 h and 7 d curing time at 23°C / 50% relative humidity;
[0090] and
[0091] Determination of "Tensile properties: strength, elongation and E modulus" according to DIN EN ISO 527-1.
[0092] Table 4
[0093]
[0094] To analyze the effect of fast curing agents on the performance of the decking, the reduction in decking height within 20 minutes or the open time of the adhesive has been linearly approximated. Figure 1 A linear fit was used to infer the plating height at t = 0.
[0095] The linear approximate plate height of 7.3 mm at 0 min for Comparative Example A is higher than the linear approximate plate height of 6.5 mm for Inventive Example 8. Adding 10% of Jeffamine SD-2001 secondary polyether diamine to the accelerator component reduces the initial plate height by 11%.
[0096] like Figure 2 As shown, for Example 10, the addition of 20% of Jeffamine SD-2001 (a secondary polyether diamine) further reduces the linear approximate deck height to 5.5 mm at 0 min. This increases the initial deck height by even 1.8 mm or 25% relative height. In addition to the positive effect on the initial deck height, both formulations show improved impact peel strength after 15 and 30 minutes compared to Comparative Example A, due to the faster reaction of the curing agent at that time resulting in a higher conversion rate.
[0097] Examples 9 and 11 use the polyol component Example 6 of the present invention containing triethanolamine as a fast curing agent. The linear approximate plank height at 0 min is 5.3 mm and 5.0 mm comparable values ( Figure 2 ), and significantly lower than 7.3 mm for comparative polyol component Example 3. Trifunctional triethanolamine leads to faster crosslinking due to higher functionality, which leads to generally faster strength increase over time. In all examples, the open time is still sufficiently high (≥10 min).
Claims
1. An adhesive system comprising a moisture-curable adhesive, the moisture-curable adhesive comprising A) Isocyanate-terminated prepolymers and B) A curing accelerator comprising i) an isocyanate-reactive compound, the isocyanate-reactive compound being triethanolamine, and ii) a polyol having no primary, secondary or tertiary amino groups, or primary thiol groups, wherein the polyol comprises 1,4-butanediol; and, The isocyanate-reactive compound (i) is present in an amount less than 5% by weight of the curing accelerator (B).
2. The adhesive system of claim 1, wherein the polyol (ii) is butanediol.
3. The adhesive system of claim 1 or 2, wherein the curing accelerator is substantially free of water.
4. The adhesive system of claim 1 or 2, wherein the prepolymer comprises an isocyanate-terminated polyether prepolymer.
5. The adhesive system of claim 1 or 2, wherein the isocyanate-terminated polyether prepolymer comprises a polyether backbone comprising ethylene oxide, propylene oxide, or a combination of these.
6. The adhesive system of claim 1 or 2, wherein the moisture-curable adhesive further comprises one or more of a filler, a plasticizer, a polyisocyanate monomer or oligomer, or a catalyst.
7. The adhesive system of claim 1 or 2, wherein the moisture curable adhesive comprises a plasticizer that is linear, branched, or a combination thereof.
8. A method for accelerating the curing of an adhesive composition, the method comprising: a) providing a moisture-curable adhesive composition comprising A) Isocyanate-terminated prepolymers and B) A curing accelerator comprising i) an isocyanate-reactive compound, the isocyanate-reactive compound being triethanolamine, and ii) a polyol having no primary, secondary or tertiary amino groups, or primary thiol groups, wherein the polyol comprises 1,4-butanediol; wherein the isocyanate-terminated prepolymer and the curing accelerator are provided separately; b) mixing the curing accelerator and the isocyanate-terminated prepolymer to form an adhesive mixture; c) applying the adhesive mixture to at least a portion of a first substrate; d) contacting the substrate having the adhesive mixture thereon with a second substrate such that the adhesive mixture is therebetween; and e) curing the adhesive mixture to bond the substrates together; The isocyanate-reactive compound (i) is present in an amount less than 5% by weight of the curing accelerator (B).
9. The method of claim 8, wherein step b) is performed using a 1K application gun or an automatic application device from a roller.
10. The method according to claim 8 or 9, wherein: The first substrate is a substrate wherein at least a portion of the substrate is optically transparent, and the second substrate is a vehicle or a building.
11. The method of claim 10, wherein: The first substrate has an opaque portion in which the adhesive mixture is applied and in contact with the second substrate.
12. The method of claim 11, wherein: The first substrate is glass or polycarbonate.
Citation Information
Patent Citations
Polyurethane composition with high early strength
CA2564992A1
Two-component polyurethane composition having high early strength
EP1524282A1
Polyurethane sealant-primer system isocyanate-reactive surface primer composition for polyurethane sealants
US3707521A
Polyurethane sealant-primer system
US3779794A
Bonding method employing moisture curable polyurethane polymers
US4687533A